Validation of Questionnaires and the Effect of Educational Videos on the Knowledge of Hyperlipidemia Patients at Banjarbaru Utara Primary Health Care - Silviana, Mega; Mafruhah, Okti Ratna; Ningrum, Vitarani Dwi Ananda (Baiman Bauntung Batuah Center, 2024)
Hyperlipidemia patients have a high risk of cardiovascular disease and stroke. Low patient knowledge causes therapy failure. Education can be provided to overcome this problem. No questionnaire instrument can measure the level of knowledge of hyperlipidemia patients. The level of knowledge of hyperlipidemia patients at Banjarbaru Utara Primary Health Care has never been studied. The research aimed to validate the questionnaire and determine the effect of educational videos on patient knowledge at the Banjarbaru Utara Primary Health Care, Banjarbaru City, South Kalimantan. The research method used to validate the questionnaire was cross-sectional, while to determine the effect of educational videos on the patient's level of knowledge using a quasi-experimental method using One Group Pre – Post Design. The research was conducted in January – March 2024 at Banjarbaru Utara Primary Health Care. The study involved eight experts, 40 patients in questionnaire validation, and 100 patients to determine the effect of educational videos. The results of questionnaire content validation show that the Content Validity Ratio (CVR) value is in the range of 0.750 – 1.000, while the Content Validity Index (CVI) value is in the range of 0.875 – 1.000. The validity test with Person Correlation shows that ten out of 20 statements on the questionnaire are considered valid (>0.312). The Cronbach's Alpha value is 0.655, indicating the questionnaire is reliable. The patient's knowledge before being given the educational video had a score of 5.96 (scale 1 – 10), while after it, it had a score of 8.73. There was an increase in the level of knowledge, reaching 46.47%. The conclusion is that the Hyperlipidemia Knowledge Questionnaire (HKQ), which consists of 10 statements, is declared valid and reliable. Educational videos significantly influence (p-value 0.000) in increasing knowledge of hyperlipidemia patients.